Hybrid Beats Classical: Why BetaSutte Dominates ARIMA for Emerging Market Inflation Forecasting During Supply Shocks - Ansari Saleh Ahmar (PT Mattawang Mediatama Solution, 2025)
This study demonstrates that hybrid trend-decomposition forecasting (BetaSutte) substantially outperforms classical ARIMA(1,1,1) methods for inflation prediction in emerging markets experiencing supply-shock-driven regime changes. Using Indonesian central bank inflation data spanning September 2021 through October 2024 (50 monthly observations), we partition the sample into 40 in-sample training observations (capturing the Russia-Ukraine supply shock peak of August 2022 at 7.71% and its policy-driven deflation) and 10 out-of-sample evaluation observations (January–October 2024, the critical disinflation recovery phase). BetaSutte achieves out-of-sample RMSE of 0.3516% compared to ARIMA's 0.5377%—a 34.6% reduction in forecast error. Critically, while BetaSutte's in-sample RMSE is 1.73× larger than ARIMA's (4.01 vs. 2.32), this apparent weakness reflects superior generalization: the model deliberately prioritizes trend signal extraction over training-data fitting, discarding noise to minimize out-of-sample prediction errors. The reversal from inferior in-sample to dominant out-of-sample performance is a defining characteristic of parsimonious hybrid methods operating under structural breaks. We attribute BetaSutte's superiority to its explicit decomposition of trend and transitory components, which captures the nonstationary deflation path better than ARIMA's differencing-based approach when regime transitions occur. Policy implications are substantial: central banks targeting inflation via published rate paths can improve forecast-based monetary decisions by adopting hybrid methods. This finding challenges the conventional dominance of ARIMA in finance and economics applications and suggests that emerging market policymakers should evaluate model choice based on out-of-sample rather than in-sample metrics when designing inflation forecasts. The paper provides empirical evidence for the bias-variance trade-off in time-series model selection and offers a practical methodology applicable to commodity-dependent central banks worldwide.